Fractional Order PID Controller for Minimizing Frequency Deviation in a Single and Multi-area Power System with GRC, GDB and Time Delay - Ahmed Mohammed Saba (Universitas Muhammadiyah Yogyakarta, 2022)
In this paper, a Fractional Order PID (FOPID) controller to minimize frequency deviation in a single and two area power system is presented. Minimizing high frequency deviation in the presence of physical constraints is very paramount in load frequency control. This is because large frequency deviation can cause the transmission line to be overloaded which may damage equipment’s at the distribution level and the mechanical devices at the generating stations. In this paper, power system with physical constraints such as Communication Delay, Governor Dead Band (GDB) and Generation Rate Constraint (GRC) were considered and modeled appropriately. An anti-windup scheme was employed to limit the effects of these physical constraints on the power system. The proposed Fractional Order PID controller was designed using the Fractional Order Modeling and Control (FOMCON) toolbox available in MATLAB/Simulink. Antlion Optimization algorithm was used to optimize the gains of the FOPID controller by minimizing Integral Square Error (ISE) as the objective function. The Integral Square Error to be minimized is the summation of the errors in frequency deviation, tie-line power deviation and the area control error. Simulation results using the proposed approach were compared with other designed methods available in literatures. Simulations were first conducted on power system designed without physical constraints, and results obtained outperformed other designed methods available in literatures for one and two area power system. Three physical constraints were then added to the proposed method, and results obtained were compared with other designed method available in literatures for power system without physical constraints. The proposed method outperformed other designed method in minimizing frequency deviation, tie-line power deviation and area control errors. However, the proposed FOPID controller took a longer time to balance the generated power and load demand when compared to other designed method for power system without physical constraints